FcγRIIa polymorphism in systemic lupus erythematosus. Issue 12 (1st December 1997) - Smyth, L J C; Snowden, N; Carthy, D; Papasteriades, C; Hajeer, A; Ollier, W E R
Abstract : OBJECTIVES: Polymorphism of the phagocyte IgG receptor FcγRIIa may modulate immune complex mediated inflammation, particularly when immune complexes contain IgG2. Previous studies suggest that this polymorphism may be an important risk factor for lupus nephritis. FcγRIIa is biallelic, the alleles R and H each having a gene frequency of about 50%. Nephritis has been associated with an increased frequency of the R allele. The frequency of common FcγRIIa alleles was examined in white subjects from the United Kingdom and Greek subjects with systemic lupus erythematosus (SLE) and healthy controls. METHODS: FcγRIIa genotyping was performed using a single step polymerase chain reaction technique, which differentiates the two major alleles, R and H. Two study populations were examined: (a) white subjects from the United Kingdom : 66 controls and 81 with SLE (19 of whom had renal disease) and (b) Greek: 52 controls and 42 with SLE (19 with renal disease). RESULTS: No significant relation was observed between FcγRIIa genotype and susceptibility to SLE or SLE nephritis. CONCLUSIONS: The FcγRIIa R allele does not seem to be associated with SLE (with or without renal disease) in our United Kingdom white or Greek populations.